Estudo da dinâmica do escoamento gás-sólido em resfriadores de catalisador de FCC usando fluidodinâmica computacional (CFD) - Lucar Monzón, Edgar Manuel (2017)
The fluid catalytic cracking (FCC) is an important process in oil industry, since it converts heavier fractions in lighter ones, which are more valuable. The catalyst particles (typically m) are deactivated during the reacting process and need to be regenerated before returning to the reactor. Temperature is a key factor that promotes coke formation and deactivation inside the reactor. As a consequence, it is necessary to cool down the solid catalyst particles before returning them to the reactor. The cooling system is usually outside the regenerator in a specific designed heat exchanger, that uses water as cold fluid. The catalyst cooler was not much studied before and many contributions can be made for improvements and intensification. The goal of this work was to contribute with this topic, using Computational Fluid Dynamics (CFD) to evaluate the gas-solid flow behavior in characteristic geometries of the catalyst cooler. Commercial package Fluent by ANSYS v14.5 was used during simulation and Eulerian model was applied for the solid phase. The volume fraction phase for the solid phase, solid and gas velocities were evaluated and described. The results were compared in terms of gas-solids flow in different geometries and showed a hydrodynamic explanation different from that currently used by the authors to justify the intensification of thermal exchange in this type of equipment. In short, longer solid-wall contact time will be primarily responsible for efficient heat transfer.